Efektivitas Edukasi Perpajakan Melalui Program Kelas Pajak Seputar E-Faktur Dan PKP “Kang Kasep” Dalam Rangka Meningkatkan Kepatuhan Wajib Pajak - Difa Nur Asyiami; Mira Permata Sari (Institut Ilmu Sosial dan Manajemen STIAMI, 2026)
Tax compliance remains a challenge at KPP Pratama Bekasi Utara, where the number of Taxable Entrepreneurs (PKP) has grown from 3,489 (2021) to 4,654 (September 2025) amid the transition from the e-Faktur system to the Coretax Administration System. This situation prompted KPP Pratama Bekasi Utara to establish the Tax Class Program on e-Faktur and PKP known as